Industrial noise: A new stimulus for dental pulp aging? Qualitative and quantitative analysis in Wistar rat teeth–A pilot study - Maria Alzira Cavacas; Maria Alzira Cavacas; Maria Alzira Cavacas; Carolina Doroteia; Ana Margarida Leonardo; Luís Proença; Luís Proença; Vítor Tavares; Vítor Tavares (Frontiers in Oral Health, 2022)
Morphological changes induced by industrial noise have been experimentally observed in several organs. This study aims to characterize the effect of industrial noise on the pulp cell density of Wistar rats from a histological point of view, through qualitative and quantitative analysis. The histologic sections were observed over the optical microscope and photographed using 10x and 40x magnifications and analyzed using an image processing software. They refer to a group of animals exposed to industrial noise for 3 months and for 7 months (EG) and another group of animals kept in silence for control (CG) during the same periods. There was a significant decrease in pulp cell density in teeth of the animals exposed for 3 months when compared to control teeth group (p = 0.01). However, in the group exposed for 7 months, no statistically significant differences were found (p = 0.66). Even so, we found an evident relationship between exposure to industrial noise and teeth morphological changes. The observed changes are similar to the modifications found on aged teeth. Therefore, this study places industrial noise as an aggressive stimulus that can cause a reaction of the pulp-dentin complex with morphological changes compatible with premature aging of the tooth.